Herpes Simplex Virus Type II Infection of Ileum Mesothelium: A Case Report and Review of the Literature - SAC Medlicott; VG Falck; KB Laupland; M Akbari; PL Beck (Canadian Journal of Gastroenterology)
Disseminated herpes simplex virus (HSV) infection usually manifests in the immunocompromised. However, anecdotal examples of visceral HSV disease and viremia have complicated type I diabetes. A case of a 53-year-old type I diabetic patient with bowel obstruction one week subsequent to bronchitis is reported. At laparotomy, a perforated segment of ileum was associated with an adhesive peritoneal band. HSV cytopathic atypia and HSV immunohistochemical staining were confined to fibrocytes and mesothelial cells without involvement of the epithelium. Dissemination of symptomatic HSV pneumonia was verified by histology, immunohistochemistry, in situ hybridization, polymerase chain reaction and direct fluorescence antibody. Intravenous acyclovir resolved symptoms. This is a novel documentation of HSV complicating ileal adhesive band disease. Furthermore, this case indicates that the HSV cytopathic effect is not unique to the epithelium. Disseminated infection can manifest in myofibrocytes and mesothelium, distinguishing it from standard epithelial atypia of localized HSV infection.